Polybutylene terephthalate resin composition

A polybutylene terephthalate resin composition combining modified polybutylene terephthalate, polycarbonate, glass flakes, and carbon black addresses the challenge of achieving excellent jet blackness and low glossiness with minimal unevenness, suitable for optical and display equipment.

JP2025062503AActive Publication Date: 2025-04-14POLYPLASTICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023171632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14
Estimated Expiration
2043-10-02

Smart Images

  • Figure 2025062503000001
    Figure 2025062503000001
  • Figure 2025062503000002
    Figure 2025062503000002
Patent Text Reader

Abstract

To provide a polybutylene terephthalate resin composition which is excellent in jet-blackness, is reduced in gloss unevenness and has low glossiness.SOLUTION: A polybutylene terephthalate resin composition contains (A) a polybutylene terephthalate resin, (B) a polycarbonate resin, (C) a glass flake, and (D) carbon black, wherein (A) the polybutylene terephthalate resin contains (a1) a modified polybutylene terephthalate resin containing 5 to 30 mol% of a comonomer unit, (C) the glass flake has average thickness of 1 μm or less and a median size of 5 to 70 μm or less, and with respect to 100 pts.mass of (A) the polybutylene terephthalate resin, a content of (B) the polycarbonate resin is 60 to 100 pts.mass, a content of (C) the glass flake is 60 to 100 pts.mass, and a content of (D) the carbon black is 0.8 to 15 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a polybutylene terephthalate resin composition. [Background technology]

[0002] Components of optical devices such as drive recorders, backup cameras, and ADAS mounted on vehicles such as automobiles, and components of display devices such as head-up displays, liquid crystal meters, and car navigation systems are required to have low gloss in order to reduce glare due to reflection, etc. Many plastic materials form a high-gloss surface when molded, so low gloss is achieved by providing a texture on the mold used for injection molding to give the molded product surface a textured finish, or by coating the molded product surface with a matting agent. Attempts to achieve low gloss by the properties of the material itself are described in, for example, Patent Documents 1 and 2. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2008-540803 [Patent Document 2] JP 2018-144581 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a polybutylene terephthalate resin composition having excellent jet-blackness and low gloss with little gloss unevenness. [Means for solving the problem]

[0005] The present disclosure encompasses the following aspects. [1] A composite material comprising: (A) a polybutylene terephthalate resin; (B) a polycarbonate resin; (C) glass flakes; and (D) carbon black; (A) the polybutylene terephthalate resin contains (a1) a modified polybutylene terephthalate resin containing 5 to 30 mol % of a comonomer unit, (C) the average thickness of the glass flakes is 1 μm or less and the median diameter is 5 to 70 μm; (A) per 100 parts by mass of polybutylene terephthalate resin (B) the content of the polycarbonate resin is 60 to 100 parts by mass, (C) the content of glass flakes is 60 to 100 parts by mass, (D) A polybutylene terephthalate resin composition having a carbon black content of 0.8 to 15 parts by mass. [2] (F) The polybutylene terephthalate resin composition according to [1], further comprising a phosphorus-based compound. [3] A molded article comprising the resin composition according to [1] or [2]. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a polybutylene terephthalate resin composition having excellent jet-blackness and low gloss with little uneven gloss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made within the scope of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. In addition, the lower and / or upper limit values ​​of the numerical range described in this disclosure are numerical values ​​within the numerical range and may be replaced with numerical values ​​shown in the examples. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments. Each configuration and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of configurations are possible as appropriate without departing from the spirit of this disclosure.

[0008] [Polybutylene terephthalate resin composition] The polybutylene terephthalate resin composition of the present disclosure (hereinafter also simply referred to as "resin composition") contains (A) a polybutylene terephthalate resin, (B) a polycarbonate resin, (C) glass flakes, and (D) carbon black, (A) the polybutylene terephthalate resin contains (a1) a modified polybutylene terephthalate resin containing 5 to 30 mol % of a comonomer unit, (C) the average thickness of the glass flakes is 1 μm or less and the median diameter is 5 to 70 μm; (A) per 100 parts by mass of polybutylene terephthalate resin (B) the content of the polycarbonate resin is 60 to 100 parts by mass, (C) the content of glass flakes is 60 to 100 parts by mass, (D) The carbon black content is 0.8 to 15 parts by mass.

[0009] When light is incident on the surface of a molded article, the phenomenon of reflection, transmission, and absorption of light occurs. From the viewpoint of increasing the absorption of light and reducing the reflection of light on the surface of a molded article, it is preferable that the resin composition has excellent jet blackness. Conventionally, black coloring has been performed by blending carbon black into a resin composition, but depending on the composition of the resin composition, sufficient jet blackness may not be obtained even if carbon black is blended. In addition, since the glossiness increases when there is a lot of reflected light on the surface of the molded article, it is preferable to reduce the reflected light. It is expected that the light is taken into the inside of the molded article by increasing the light transmittance of the resin material, and the reflected light is reduced, but if the light transmittance is too high, the glossiness may increase or the jet blackness may decrease. Furthermore, if the injection speed changes when the resin composition is injection molded, the glossiness of the molded article obtained may become uneven. In particular, in molded articles having complex shapes, the filling speed of the resin varies depending on the part of the molded article even when multi-stage speed control is performed, so that the glossiness of the molded article obtained may become uneven. The resin composition of the present disclosure has the above-described configuration, and thus can achieve both excellent jet blackness and low gloss, and can provide a molded product with little gloss unevenness.

[0010] In the present disclosure, the term "polybutylene terephthalate resin composition" refers to a resin composition containing a polybutylene terephthalate resin. The content of the polybutylene terephthalate resin will be described later.

[0011] <(A) Polybutylene terephthalate resin> The (A) polybutylene terephthalate resin contains (a1) a modified polybutylene terephthalate resin containing 5 to 30 mol % of a comonomer unit (hereinafter, also simply referred to as "(a1) modified polybutylene terephthalate resin"). By containing the (a1) modified polybutylene terephthalate resin, a polybutylene terephthalate resin composition having excellent jet blackness and low glossiness with little gloss unevenness can be obtained. In addition, the jet blackness can be further enhanced by blending carbon black.

[0012] (a1) The modified polybutylene terephthalate resin contains terephthalic acid or its ester-forming derivative (C 1-6 The copolymer has as its main component polybutylene terephthalate obtained by polycondensation reaction of alkylene glycol having 4 carbon atoms (1,4-butanediol) or its ester-forming derivative (acetylated product, etc.) as a glycol component, and another comonomer component (third component) is introduced in an amount of 5 to 30 mol % (preferably 7 to 25 mol %, more preferably 8 to 20 mol %, further preferably 10 to 15 mol %, for example 10 to 13 mol %) relative to 100 mol % of all dicarboxylic acid components. The other comonomer component (third component) means a copolymerizable monomer component different from terephthalic acid or its ester-forming derivative, and 1,4-butanediol or its ester-forming derivative. The content of the comonomer component (third component) in the (a1) modified polybutylene terephthalate resin can be measured, for example, by 1 It can be measured using H-NMR.

[0013] Examples of dicarboxylic acid components that can be used as other comonomer components (third components) include C carboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-dicarboxydiphenyl ether. 8-14 Aromatic dicarboxylic acids; succinic acid, adipic acid, azelaic acid, sebacic acid, etc. 4-16 Alkanedicarboxylic acids such as cyclohexanedicarboxylic acid, etc. 5-10 Cycloalkanedicarboxylic acids; ester-forming derivatives of these dicarboxylic acid moieties (C 1-6 These dicarboxylic acid components can be used alone or in combination of two or more kinds.

[0014] Among these dicarboxylic acid components, C 8-12 Aromatic dicarboxylic acids such as adipic acid, azelaic acid, and sebacic acid 6-12 The alkanedicarboxylic acids of the formula (I) are more preferred.

[0015] Examples of glycol components that can be used as other comonomer components (third components) include C glycols such as ethylene glycol, propylene glycol, trimethylene glycol, 1,3-butylene glycol, hexamethylene glycol, neopentyl glycol, and 1,3-octanediol. 2-10 alkylene glycols; polyoxyalkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol; alicyclic diols such as cyclohexanedimethanol and hydrogenated bisphenol A; aromatic diols such as bisphenol A and 4,4'-dihydroxybiphenyl; C diols of bisphenol A such as 2-mol ethylene oxide adduct of bisphenol A and 3-mol propylene oxide adduct of bisphenol A 2-4 or ester-forming derivatives of these glycols (acetylated products, etc.). These glycol components can be used alone or in combination of two or more.

[0016] Among these glycol components, C ethylene glycol, trimethylene glycol, etc. 2-6 More preferred are alkylene glycols such as those mentioned above, polyoxyalkylene glycols such as diethylene glycol, and alicyclic diols such as cyclohexanedimethanol.

[0017] Examples of the comonomer component (third component) that can be used in addition to the dicarboxylic acid component and the glycol component include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and 4-carboxy-4'-hydroxybiphenyl; aliphatic hydroxycarboxylic acids such as glycolic acid and hydroxycaproic acid; C hydroxycarboxylic acids such as propiolactone, butyrolactone, valerolactone, and caprolactone (ε-caprolactone, etc.); 3-12 Lactones; ester-forming derivatives of these comonomer components (C 1-6 Examples of the alkyl ester derivatives, acid halides, acetylated derivatives, etc. of the above-mentioned compounds include the above-mentioned compounds.

[0018] Any of the polybutylene terephthalate copolymers produced by polycondensing the above compounds as comonomer components can be suitably used as the (a1) modified polybutylene terephthalate resin. In one embodiment, the (a1) modified polybutylene terephthalate resin preferably contains an isophthalic acid modified polybutylene terephthalate copolymer and / or an alkylene (excluding 1,4-butanediol) modified polybutylene terephthalate copolymer, and more preferably contains an isophthalic acid modified polybutylene terephthalate copolymer. The (a1) modified polybutylene terephthalate resin may be used alone or in combination of two or more kinds.

[0019] The content of the (a1) modified polybutylene terephthalate resin is preferably 80 to 100 mass%, more preferably 85 to 100 mass%, further preferably 90 to 100 mass%, and particularly preferably 95 to 100 mass%, in the total amount (100 mass%) of the (A) polybutylene terephthalate resin. In one embodiment, the (A) polybutylene terephthalate resin may be composed only of the (a1) modified polybutylene terephthalate resin.

[0020] In one embodiment, the polybutylene terephthalate resin (A) may contain, in addition to the modified polybutylene terephthalate resin (a1), a homopolybutylene terephthalate polymer (a2) (unmodified polybutylene terephthalate resin). The content of the homopolybutylene terephthalate polymer (a2) may be 0 to 20 mass%, 0 to 10 mass%, or 0 to 5 mass% in the total amount (100 mass%) of the polybutylene terephthalate resin (A).

[0021] From the viewpoint of improving moldability, the intrinsic viscosity of the (A) polybutylene terephthalate resin is preferably 0.65 to 1.15 dL / g, more preferably 0.67 to 1.00 dL / g. The intrinsic viscosity can also be adjusted by blending polybutylene terephthalate resins having different intrinsic viscosities. For example, a polybutylene terephthalate resin having an intrinsic viscosity of 0.9 dL / g can be prepared by blending a polybutylene terephthalate resin having an intrinsic viscosity of 1.0 dL / g with a polybutylene terephthalate resin having an intrinsic viscosity of 0.7 dL / g. The intrinsic viscosity of the (A) polybutylene terephthalate resin is a value measured in o-chlorophenol at a temperature of 35°C using an Ubbelohde viscometer.

[0022] The amount of terminal carboxyl groups (CEG) of the polybutylene terephthalate resin (A) is not particularly limited as long as it does not impede the object of the present disclosure, but is preferably 5 to 30 meq / kg, more preferably 10 to 25 meq / kg. By using a polybutylene terephthalate resin having an amount of terminal carboxyl groups in this range, it is possible to suppress the decrease in strength of the resulting polybutylene terephthalate resin composition in a humid and hot environment.

[0023] The content of the (A) polybutylene terephthalate resin in the total amount (100 mass%) of the resin composition is preferably from 20 to 60 mass%, more preferably from 25 to 50 mass%, and even more preferably from 30 to 40 mass%.

[0024] As described later, the resin composition may contain a thermoplastic resin other than the polybutylene terephthalate resin (A) and the polycarbonate resin (B), but from the viewpoint of easily obtaining a polybutylene terephthalate resin composition having excellent jet blackness and low gloss with little gloss unevenness, the total content of the polybutylene terephthalate resin (A) and the polycarbonate resin (B) is preferably 80 to 100 mass%, more preferably 85 to 100 mass%, further preferably 90 to 100 mass%, and particularly preferably 95 to 100 mass% in the total amount (100 mass%) of the thermoplastic resins constituting the resin composition. In one embodiment, the thermoplastic resin contained in the resin composition may be composed only of the polybutylene terephthalate resin (A) and the polycarbonate resin (B).

[0025] <(B) Polycarbonate resin> The resin composition contains a polycarbonate resin (B). By containing the polycarbonate resin (B), a polybutylene terephthalate resin composition having excellent jet blackness and low gloss with little gloss unevenness can be obtained. (B) The polycarbonate resin may be a polymer obtained by reacting a dihydroxy compound with a carbonate ester such as phosgene or diphenyl carbonate. The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) may be used.

[0026] Examples of dihydroxy compounds include alicyclic compounds (eg, alicyclic diols) and bisphenol compounds, with bisphenol compounds being preferred.

[0027] Bisphenol compounds include bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3-methylphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxy-3-methylphenyl)ethane, 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)propane ("bisphenol A"), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-ethylphenyl)propane, 2,2-bis(4-hydroxy-3-t-butylphenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2- Bis(hydroxyaryl)C such as bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 2,2-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 2,2-bis(4-hydroxyphenyl)octane, bis(4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)dibenzylmethane, 1,1-bis(4-hydroxyphenyl)-1-phenylpropane, and 2,2,2',2'-tetrahydro-3,3,3',3'-tetramethyl-1,1'-spirobi-[1H-indene]-6,6'-diol. 1-10 Alkanes, preferably bis(hydroxyaryl)C 1-6 Alkanes; bis(hydroxyaryl) cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, etc. 4-10cycloalkanes; dihydroxyaryl ethers such as 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether; dihydroxyaryl sulfones such as 4,4'-dihydroxydiphenyl sulfone and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone; dihydroxyaryl sulfides such as 4,4'-dihydroxydiphenyl sulfide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide; dihydroxyaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide; and dihydroxyaryl ketones such as 4,4'-dihydroxydiphenyl ketone and 4,4'-dihydroxy-3,3'-dimethyldiphenyl ketone.

[0028] A preferred example of the (B) polycarbonate resin is bisphenol A polycarbonate.

[0029] The (B) polycarbonate resin may be a homopolycarbonate or a copolycarbonate, and the polycarbonate resins may be used alone or in combination of two or more kinds.

[0030] (B) The melt viscosity of polycarbonate resin is set at 300℃, 1000sec in accordance with ISO11443 from the viewpoint of fluidity. -1 The melt viscosity is preferably 0.40 kPa·s or less, more preferably 0.35 kPa·s or less, and even more preferably 0.30 kPa·s or less, using a Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd., a 1 mmφ×20 mmL / flat die as a capillary, a barrel temperature of 300°C, a shear rate of 1000 sec -1 The value measured is taken as

[0031] The content of the (B) polycarbonate resin is 60 to 100 parts by mass, preferably 65 to 95 parts by mass, more preferably 70 to 90 parts by mass, even more preferably 75 to 85 parts by mass, and particularly preferably 75 to 83 parts by mass, relative to 100 parts by mass of the (A) polybutylene terephthalate resin. By blending a predetermined amount of the (B) polycarbonate resin with the (A) polybutylene terephthalate resin, a polybutylene terephthalate resin composition having excellent jet blackness and low glossiness with little gloss unevenness can be obtained. As a non-limiting mechanism, it is considered that by blending a predetermined amount of the (B) polycarbonate resin with the (A) polybutylene terephthalate resin, transparency can be appropriately increased, and the light incident on the surface of the molded article can be transmitted into the inside of the molded article without reducing the jet blackness, and the transmitted light can be absorbed by a light absorbing material such as (D) carbon black, thereby reducing the reflected light on the surface of the molded article.

[0032] In one embodiment, the content of the (B) polycarbonate resin may be 77 parts by mass, 78 parts by mass, 80 parts by mass, 82 parts by mass, or 85 parts by mass relative to 100 parts by mass of the (A) polybutylene terephthalate resin, or may be within the upper or lower limit of the above numerical range, or may be a combination of these ranges.

[0033] <(C) Glass flakes> The resin composition contains (C) glass flakes. The glass flakes have an average thickness of 1 μm or less. The median diameter (D50) of the (C) glass flakes contained in the resin composition is 5 to 70 μm. By containing (C) glass flakes having an average thickness of 1 μm or less and a median diameter of 5 to 70 μm, a polybutylene terephthalate resin composition having excellent jet blackness and low gloss with little gloss unevenness can be obtained.

[0034] The average thickness of the (C) glass flakes is preferably 0.9 μm or less, more preferably 0.8 μm or less, and may be 0.7 μm or less. In one embodiment, the average thickness of the (C) glass flakes may be 0.01 to 1 μm, 0.05 to 1 μm (e.g., 0.05 to 0.9 μm, 0.05 to 0.8 μm, or 0.05 to 0.7 μm), or 0.1 to 1 (e.g., 0.1 to 0.9 μm, 0.1 to 0.8 μm, 0.1 to 0.7 μm, 0.7 to 1 μm, or 0.7 to 0.9 μm). The average thickness of the (C) glass flakes may be calculated from the raw material manufacturer's value or by measurement. For example, it can be calculated by analyzing images taken with a CCD camera using a 2-propanol solvent with a dynamic image analysis method / particle (state) analyzer PITA-3 manufactured by Seishin Enterprise Co., Ltd., and calculating the weighted average. The average value may also be determined by direct observation using an electron microscope or the like. The average thickness of the (C) glass flakes in the experimental data is a value measured by the above method for the (C) glass flakes in the resin composition.

[0035] The median diameter (D50) of the glass flakes (C) contained in the resin composition is 5 to 70 μm, preferably 10 to 60 μm, and more preferably 20 to 50 μm. In one embodiment, the median diameter of the glass flakes (C) may be 40 μm or 41 μm, or may be within the upper or lower limit of the above numerical range. In the present disclosure, the median diameter refers to the median diameter of the (C) glass flakes in the resin composition measured by a laser diffraction / scattering method (e.g., LA-960 manufactured by Horiba, Ltd.) The median diameter of the (C) glass flakes in the resin composition can be measured by treating the resin composition or a molded product thereof in an electric furnace at 600°C for 4 hours and measuring the remaining residue by the laser diffraction / scattering method.

[0036] The average aspect ratio of the (C) glass flakes is not limited within a range that does not impair the effects of the present disclosure, and is preferably 5 to 200, more preferably 20 to 150, and even more preferably 30 to 100. The average aspect ratio is used here as an index representing the anisotropy of the plate shape, and is the ratio of the median diameter to the average thickness (aspect ratio = median diameter / average thickness). The median diameter can be measured by a laser diffraction / scattering method (LA-960 manufactured by Horiba, Ltd.) or the like. Alternatively, the ratio of the particle diameter to the thickness may be calculated by direct observation using an electron microscope or the like, and the average value may be calculated. The median diameter and aspect ratio of the (C) glass flakes are values ​​measured by the above-mentioned method for the (C) glass flakes remaining as residues after treating a molded product made of a resin composition in an electric furnace at 600°C for 4 hours.

[0037] The content of the (C) glass flakes is 60 to 100 parts by mass, preferably 65 to 95 parts by mass, more preferably 70 to 90 parts by mass, even more preferably 75 to 85 parts by mass, and particularly preferably 75 to 83 parts by mass, relative to 100 parts by mass of the (A) polybutylene terephthalate resin. By blending a predetermined amount of (C) glass flakes having a predetermined thickness and a predetermined median diameter in the resin composition with the (A) polybutylene terephthalate resin, a polybutylene terephthalate resin composition having excellent jet blackness and low glossiness with little gloss unevenness can be obtained. As a non-limiting mechanism, it is considered that the (C) glass flakes having a predetermined thickness and median diameter are easily broken into an amorphous shape during molding to form a surface with no regularity, and are easily roughened to a matte finish with fine irregularities by blending them in a predetermined amount, which causes light to be reflected randomly. When light is reflected randomly, the reflected light is repeatedly taken in and absorbed inside the molded product, thereby attenuating it, which is thought to achieve a low gloss with little gloss unevenness without reducing the jet black color.

[0038] In one embodiment, the content of the (C) glass flakes may be 77 parts by mass, 78 parts by mass, 80 parts by mass, 81 parts by mass, or 85 parts by mass relative to 100 parts by mass of the (A) polybutylene terephthalate resin, or may be within the range in which these are the upper or lower limit values ​​of the above-mentioned numerical range, or may be a range combining these.

[0039] The resin composition may contain a filler other than the (C) glass flake, as described later, but from the viewpoint of easily obtaining a polybutylene terephthalate resin composition having excellent jet blackness and low gloss with little gloss unevenness, the content of the (C) glass flake is preferably 80 to 100 mass%, more preferably 85 to 100 mass%, further preferably 90 to 100 mass%, and particularly preferably 95 to 100 mass% of the total amount (100 mass%) of the inorganic filler contained in the resin composition. In one embodiment, the inorganic filler contained in the resin composition may be composed only of the (C) glass flake.

[0040] <(D) Carbon black> The resin composition contains (D) carbon black. Examples of (D) carbon black include furnace black, ketjen black, channel black, acetylene black, thermal black, etc. (D) carbon black can be used alone or in combination of two or more. (D) carbon black may be used as a pigment (or colorant).

[0041] (D) The dibutyl phthalate (DBP) oil absorption of carbon black is 30 to 600 cm from the viewpoint of blackness and light absorption. 3 / 100g is preferable, 40 to 550cm 3 / 100g is more preferable, 50 to 500cm 3 In one embodiment, the DBP oil supply amount of the (D) carbon black is 40 to 100 cm 3 / 100g (e.g., 50-80cm 3 / 100g), 100cm3 / Over 100g 500cm 3 / 100g or less (e.g., 100~495cm 3 The dibutyl phthalate oil absorption is a value measured in accordance with JIS K6217-4:2008.

[0042] The average particle size of the (D) carbon black is preferably 5 to 100 nm, more preferably 8 to 50 nm, and further preferably 10 to 40 nm. In one embodiment, the average particle size of the (D) carbon black is preferably 8 to 30 nm, more preferably 10 to 30 nm, from the viewpoint of increasing the jet blackness of the molded article and easily giving a molded article with high light absorption. In one embodiment, the average particle size of the (D) carbon black may be 13 nm, 16 nm, 22 nm, or 34 nm, or may be within the range of the upper or lower limit of the above numerical range, or may be within a combination of these ranges. The average particle size is the arithmetic average particle size determined by observing 1,000 particles of carbon black under an electron microscope before the carbon black is blended into the resin composition.

[0043] The content of (D) carbon black is 0.8 to 15 parts by mass (e.g., 0.9 to 15 parts by mass, or 1 to 15 parts by mass) and preferably 0.8 to 12 parts by mass (e.g., 0.9 to 12 parts by mass, or 1 to 12 parts by mass) relative to 100 parts by mass of (A) polybutylene terephthalate resin. By including (D) carbon black in an amount of 0.8 to 15 parts by mass relative to 100 parts by mass of (A) polybutylene terephthalate resin, a polybutylene terephthalate resin composition having excellent jet blackness and low gloss with little gloss unevenness can be obtained. From the viewpoint of easily obtaining a polybutylene terephthalate resin composition having better jet blackness, less uneven glossiness, and better low glossiness, the content of (D) carbon black is more preferably 0.8 to 11 parts by mass (0.9 to 11 parts by mass, 1 to 11 parts by mass), more preferably 0.8 to 10 parts by mass, even more preferably 0.8 to 8 parts by mass, and may be 1 to 6 parts by mass, relative to 100 parts by mass of (A) polybutylene terephthalate resin. In one embodiment, the content of (D) carbon black may be 1.3 parts by mass, 2.6 parts by mass, or 5.3 parts by mass, relative to 100 parts by mass of (A) polybutylene terephthalate resin, or may be within the range of the upper limit or lower limit of the above numerical range, or may be within a combination of these ranges.

[0044] <(F) Phosphorus compounds> The resin composition may contain a phosphorus-based compound (F) as required, which can improve the mold releasability during injection molding and the heat resistance of the molded product.

[0045] Examples of the phosphorus-based compound include organic phosphite-based compounds, organic phosphonite-based compounds, alkali metal phosphates, and alkaline earth metal phosphates. Examples of the organic phosphite compound include bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis(nonylphenyl)pentaerythritol diphosphite. An example of the organic phosphonite compound is tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylene phosphonite. Examples of the alkali metal phosphate include alkali metal salts such as potassium phosphate and sodium phosphate [sodium monophosphate (sodium dihydrogen phosphate), sodium disodium phosphate (sodium hydrogen phosphate, sodium monohydrogen phosphate, disodium hydrogen phosphate, etc.)]. Examples of alkaline earth metal phosphates include alkaline earth metal salts such as calcium phosphate [monocalcium phosphate (calcium dihydrogen phosphate, calcium bis(dihydrogen phosphate) monohydrate, etc.), secondary calcium phosphate (calcium hydrogen phosphate, calcium hydrogen phosphate dihydrate, etc.)], and magnesium phosphate (magnesium hydrogen phosphate, magnesium dihydrogen phosphate, etc.). The alkali metal salt or alkaline earth metal salt may be either anhydrous or hydrated. (F) The phosphorus-based compound may be used alone or in combination of two or more kinds.

[0046] Of these phosphorus-based compounds, one or more selected from alkali metal phosphates, alkaline earth metal phosphates, and organic phosphites are preferred.

[0047] The content of the (F) phosphorus-based compound is preferably from 0.01 to 2.0 parts by mass, and more preferably from 0.05 to 1.0 part by mass, relative to 100 parts by mass of the (A) polybutylene terephthalate resin.

[0048] (Other resin components) The resin composition may contain other thermoplastic resins other than the polybutylene terephthalate resin (A) and the polycarbonate resin (B) within a range that does not impair the effects of the present disclosure. Examples of other thermoplastic resins include polyethylene terephthalate and acrylonitrile styrene resin. The content of the other thermoplastic resin is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and may be 0 to 5 parts by mass, relative to 100 parts by mass of the polybutylene terephthalate resin (A).

[0049] The resin composition may contain an elastomer (e.g., ABS, core-shell elastomer, etc.) that is generally used to improve impact resistance, but since whitening is likely to occur if the refractive index difference between the elastomer and polybutylene terephthalate or polycarbonate is large, the refractive index of the elastomer is preferably about 1.55 to 1.60 in order to further enhance the jet blackness of the molded product. For example, a core-shell elastomer with a particle size of about 1 to 10 μm has the effect of reducing gloss, but since the acrylic resin used in the shell, etc. has a low refractive index and is likely to whiten, the content is preferably less than 2 mass%, more preferably less than 1 mass%, of the total amount (100 mass%) of the resin composition.

[0050] (Other fillers) The resin composition may contain other fillers other than the (C) glass flakes, if necessary. As the filler, a fibrous filler, a powdery filler (excluding carbon black), and a plate-like filler (excluding glass flakes) may be used depending on the purpose. The content of the other fillers is preferably 0 to 60 parts by mass, more preferably 0 to 50 parts by mass, more preferably 0 to 30 parts by mass, and may be 0 to 20 parts by mass, based on 100 parts by mass of the (A) polybutylene terephthalate resin.

[0051] Glass fibers are easily oriented in a molded product by injection molding and are not easily diffusely reflected, so that unevenness in gloss tends to occur. In one embodiment, from the viewpoint of easily realizing a polybutylene terephthalate resin composition having low gloss, the content of glass fibers in the resin composition is preferably less than 20 parts by mass, more preferably less than 10 parts by mass, further preferably less than 5 parts by mass, and particularly preferably less than 1 part by mass, relative to 100 parts by mass of the (A) polybutylene terephthalate resin.

[0052] (Additives) In addition to the above-mentioned components, the resin composition may contain known additives that are generally added to thermoplastic resins and thermosetting resins, i.e., burr inhibitors, release agents, lubricants (e.g., fatty acid esters, etc.), plasticizers, flame retardants, colorants such as dyes and pigments (excluding carbon black), crystallization accelerators, crystal nucleating agents (e.g., boron nitride, etc.), various antioxidants, heat stabilizers, weather resistance stabilizers, corrosion inhibitors, etc., within the scope of the present disclosure.

[0053] The method for preparing the resin composition is not limited, and examples thereof include a method of melt-kneading and extruding each component into pellets using a melt-kneading device such as a single-screw or twin-screw extruder, a method of preparing pellets (master batches) having different compositions and mixing the pellets in a predetermined amount, etc. The pellets may be prepared, for example, by melt-mixing the components other than the brittle component (glass flakes, etc.) and then mixing the brittle component.

[0054] The resin composition has excellent low gloss and little gloss unevenness. In one embodiment, the resin composition has a 60° gloss of 27 or less, more preferably 23 or less, as measured by JIS-Z-8741 for a molded product. In one embodiment, the resin composition has a 60° gloss of 27 or less, more preferably 23 or less, as measured by JIS-Z-8741:1997 for a molded product obtained by injection molding at an injection speed of 30 mm / s, 80 mm / s, or 120 mm / s. The gloss can be measured at an angle of 60° using a gloss meter (e.g., Handy Gloss Meter PG-II, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0055] In one embodiment, the resin composition has excellent jet blackness. In one embodiment, the resin composition has a molded product with an L* value according to JIS-Z-8781-4:2013 of preferably 14 or less, more preferably 13 or less. Since the resin composition has excellent jet blackness, it can absorb light and prevent reflection. In one embodiment, the resin composition has an L* value measured by the above method at three arbitrarily selected points of the molded product of preferably 14 or less, more preferably 13 or less.

[0056] (Application) The resin composition of the present disclosure has excellent jet blackness and low gloss with little uneven gloss, and therefore can be preferably used for manufacturing various optical device components and display device components. For example, it can be preferably used for manufacturing components used in drive recorders, backup cameras, ADAS, head-up displays, liquid crystal meters, car navigation systems, etc.

[0057] [Molded products] The molded article contains the polybutylene terephthalate resin composition described above. Since the molded article contains the polybutylene terephthalate resin composition described above, the molded article has excellent jet blackness and low gloss, and has little uneven gloss depending on the part of the molded article.

[0058] In one embodiment, the molded article has a 60° gloss according to JIS-Z-8741 of preferably 27 or less, more preferably 23 or less. In one embodiment, the molded article has a 60° gloss measured by the above method at three arbitrarily selected points of preferably 27 or less, more preferably 23 or less.

[0059] In one embodiment, the molded article has an L* value according to JIS-Z-8781-4 of preferably 14 or less, more preferably 13 or less. In one embodiment, the molded article has an L* value measured by the above method at three arbitrarily selected points of preferably 14 or less, more preferably 13 or less.

[0060] The molded product may have a textured surface to further improve its low gloss, but the inclusion of the resin composition provides excellent low gloss and little uneven gloss, so the surface does not need to be textured. The molded product may have a matting agent applied to its surface to further improve its low gloss, but the inclusion of the resin composition provides excellent low gloss and little uneven gloss, so the surface does not need to be matting. Examples of matting agents include acrylic, urethane, and epoxy paints.

[0061] The molding method for the molded product is not limited, and may be a conventional method such as extrusion molding, injection molding, compression molding, blow molding, vacuum molding, rotational molding, gas injection molding, etc., but is usually injection molding. The mold temperature during injection molding is usually about 40 to 120°C, preferably 50 to 80°C, and more preferably about 60 to 80°C. EXAMPLES

[0062] The present disclosure will be described in more detail below by showing examples, but interpretation of the present disclosure is not limited to these examples.

[0063] <Material> A-1: Polybutylene terephthalate resin (manufactured by Polyplastics Co., Ltd., intrinsic viscosity (IV) 0.69 dL / g, terminal carboxyl group amount (CEG) 16 meq / kg) A-2: Isophthalic acid modified polybutylene terephthalate resin (Polyplastics Co., Ltd., isophthalic acid 12.5 mol% modified polybutylene terephthalate resin) B: Polycarbonate resin (Teijin Ltd., Panlite L-1225L), melt viscosity (300°, 1000sec -1 ) 0.27 kPa·s C-1: Glass flakes (Nippon Sheet Glass Co., Ltd., Fine Flake MEG160FY-M01), average thickness 0.7 μm, average particle size 160 μm (manufacturer catalog value) C-2: Glass flakes (REFG-108 manufactured by Nippon Sheet Glass Co., Ltd.), average thickness 5 μm, average particle size 600 μm (manufacturer catalog value) C-3: Potassium titanate (Otsuka Chemical Co., Ltd., TISMO N102) C-4: Talc (Hayashi Kasei Co., Ltd., Micron White Upn HS-T0.8), average particle size 2.7 μm C-5: Talc (Matsumura Sangyo Co., Ltd., Crown Talc ID), average particle size 19 μm D-1: Ketjen black (Lion Specialty Chemicals Co., Ltd., EC600JD), average particle size 34 nm, DBP absorption 495 cm 3 / 100g D-2: Carbon black (Mitsubishi Chemical Corporation, Carbon Black #750B), average particle size 22 nm, DBP absorption 116 cm 3 / 100g D-3: Carbon black (Mitsubishi Chemical Corporation, Carbon Black #960B), average particle size 16 nm, DBP absorption 69 cm 3 / 100g D-4: Carbon black (Mitsubishi Chemical Corporation, carbon black #2600), average particle size 13 nm, DBP absorption 77 cm 3 / 100g E-1: Core-shell elastomer (Kaneka Corporation, Kane Ace MP90) E-2: Core-shell elastomer (Aica Kogyo Co., Ltd., Staphyloid PO-0935) F: Dibasic calcium phosphate (manufactured by Taihei Chemical Industry Co., Ltd., ester exchange inhibitor) G: Boron nitride (manufactured by Mizushima Ferroalloy Co., Ltd., nucleating agent) H: Fatty acid ester (Riken Vitamin Co., Ltd., Rikemal B-150, lubricant)

[0064] [Examples 1 to 10, Comparative Examples 1 to 21] The raw materials were mixed in the ratios shown in Tables 1 and 2, and melt-kneaded and extruded using a twin-screw extruder at a cylinder temperature of 260°C and a screw rotation of 150 rpm to prepare polybutylene terephthalate resin compositions of Examples 1 to 10 and Comparative Examples 1 to 21. The obtained polybutylene terephthalate resin composition was used to mold three flat plate-shaped molded products (dimensions: 70 mm x 50 mm x thickness 3 mm) at a cylinder temperature of 260°C, a mold temperature of 80°C, a holding pressure of 60 MPa, and an injection speed of 30 mm / s, 80 mm / s, or 120 mm / s.

[0065] [Measurement and Evaluation] The 60° gloss and lightness L* of each of the molded articles were measured by the following methods. The results are shown in Tables 1 and 2.

[0066] <60° gloss> The gloss (%) was measured in accordance with JIS-Z-8741:1997 using a handy gloss meter PG-II (60°) manufactured by Nippon Denshoku Industries Co., Ltd. Low gloss and uneven gloss were evaluated based on the following criteria. (Low gloss) 3: The gloss of all three molded products with different injection speeds is 23% or less (excellent low gloss and little gloss unevenness) 2: The gloss of all three molded products with different injection speeds is 27% or less (low gloss is good). 1: The gloss of at least one of the three molded products with different injection speeds exceeds 27% (low gloss is poor (high gloss)) (Uneven gloss) 3: The difference between the maximum and minimum gloss values ​​of three molded products with different injection speeds is 5 or less. 2: The difference between the maximum and minimum gloss values ​​of three molded products with different injection speeds is more than 5 and less than 10. 1: The difference between the maximum and minimum gloss values ​​of three moldings with different injection speeds exceeds 10.

[0067] (Lightness L*) The L* value was measured in accordance with JIS-Z-8781-4:2013 using a color computer SM-P manufactured by Suga Test Instruments Co., Ltd. The jet blackness was evaluated based on the following criteria. 3: All L* values ​​of three molded products with different injection speeds are 13 or less (excellent jet blackness) 2: All L* values ​​of the three molded products with different injection speeds are greater than 13 and less than 14 (good jet blackness) 1: At least one of the three molded products with different injection speeds has an L* value greater than 14.

[0068] (Median diameter of glass flakes) A molded article made of a polybutylene terephthalate resin composition (among the above molded articles, the molded article molded at an injection speed of 80 mm / s) was treated in an electric furnace at 600°C for 4 hours, and the median diameter of the glass flakes was calculated from the remaining residue using a laser diffraction / scattering type particle size distribution measuring device LA-960 manufactured by Horiba, Ltd.

[0069] [Table 1] [Table 2]

[0070] As shown in Table 1, the resin compositions of Examples 1 to 10 can give molded articles with excellent jet blackness and low gloss with little uneven gloss. [Industrial Applicability]

[0071] INDUSTRIAL APPLICABILITY The resin composition of the present disclosure has excellent jet-black properties and low gloss with little uneven gloss, and therefore can be preferably used for producing various optical device components and display device components, and has industrial applicability.

Claims

1. (A) polybutylene terephthalate resin, (B) polycarbonate resin, (C) glass flakes, and (D) carbon black; (A) the polybutylene terephthalate resin comprises (a1) a modified polybutylene terephthalate resin containing 5 to 30 mol % of a comonomer unit, (C) The average thickness of the glass flakes is 1 μm or less and the median diameter is 5 to 70 μm; (A) per 100 parts by mass of polybutylene terephthalate resin, (B) the content of the polycarbonate resin is 60 to 100 parts by mass, (C) the content of glass flakes is 60 to 100 parts by mass, (D) A polybutylene terephthalate resin composition having a carbon black content of 0.8 to 15 parts by mass.

2. The polybutylene terephthalate resin composition according to claim 1 , further comprising (F) a phosphorus-based compound.

3. A molded article comprising the resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Plane injected molding of polycarbonate

    JP1996229976A

  • Polybutylene terephthalate resin composition and its molded product

    JP1997104812A

  • Polybutylene terephthalate resin composition and molded article

    JP1997291204A

  • Aromatic polycarbonate resin composition and molded product comprising the same

    JP1998306206A

  • Thermoplastic resin composition

    JP2003268212A